A new species of spectacular spider wasp mimic from Thailand is the first representative of the genus Melanosphecia Le Cerf 1916 (Lepidoptera: Sesiidae: Osminiini) to be filmed in the wild - Skowron Volponi, Marta A. (Zootaxa, 2019)
A metallic blue, new species of clearwing moth from Thailand is described and shown on video. With its spectacular colouration, long hind legs and an incredible illusion of a wasp-waist, complemented by behavioural imitations, this sesiid is a striking spider wasp mimic. Notes on possible mimicry models, behaviour and conditions of occurrence are given. COI DNA barcode sequence is provided. This is the first country record of Melanosphecia Le Cerf 1916 for Thailand and the first representative of this genus to be filmed in its natural habitat.